Omnichannel Marketing dan Daya Saing Bank Perekonomian Rakyat Syariah (BPRS) Pendekatan Integrated Marketing Strategy di Era Digital - Rahmat Ramadan; Muhamad Zen; Fatmawati Fatmawati (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Bank Perekonomian Rakyat Syariah (BPRS) faces intensifying competitive pressures in the era of digital transformation, competing with Islamic commercial banks, fintech companies, and digital financial platforms. This article examines how an omnichannel marketing strategy within an Integrated Marketing Strategy (IMS) framework can strengthen BPRS competitiveness while accelerating the economic growth of Muslims in Indonesia. The study uses a Systematic Literature Review (SLR) method based on the PRISMA protocol for 25 selected articles from 87 identified through Google Scholar, Scopus, and the accredited SINTA portal ranked 1–3, with a publication period of 2022–2025. Selection was based on thematic relevance, methodological quality, and full-text accessibility. The study results show that the synergistic integration of physical, digital, and community channels can increase service reach, customer loyalty, and market penetration in the Muslim segment. The novelty of this research lies in the construction of a three-layer omnichannel model that is contextual-sharia and has not been formulated in previous literature, with maqashid sharia as the normative evaluative standard that distinguishes this approach from conventional IMS models. OJK regulations through the 2024–2027 RP2B Roadmap and the 2023 P2SK Law have created momentum for the digital transformation of BPRS, which requires a response with an integrated, technology-based marketing strategy.